2020
DOI: 10.5194/essd-2020-148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The global forest above-ground biomass pool for 2010 estimated from high-resolution satellite observations

Abstract: Abstract. The terrestrial forest carbon pool is poorly quantified, in particular in regions with low forest inventory capacity. By combining multiple satellite observations of synthetic aperture radar (SAR) backscatter around the year 2010, we generated a global, spatially explicit dataset of above-ground forest biomass (dry mass, AGB) with a spatial resolution of 1 ha. Using an extensive database of 110,897 AGB measurements from field inventory plots, we show that the spatial patterns and magnitude of AGB are… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 31 publications
0
37
1
Order By: Relevance
“…While this study and Avitabile et al [22] presented probability distribution functions skewed towards low biomass ranges, other studies [21,23,81] showed distributions tending towards much higher AGB levels, with averages two to three times larger than those found in this study and by Avitabile et al [22] (Figure 7). Figure 8 shows that the datasets from [21,23,81] did not adequately represent all the variations that exist in the area due to the lower spatial resolution and, also, generally showed a greater overestimation of the AGB. Although Santoro et al [81] provided more details in terms of the distribution of AGB in comparison with the other three maps, their map still overestimated the AGB compared to our results.…”
Section: Agb and Uncertainty Mapcontrasting
confidence: 78%
See 4 more Smart Citations
“…While this study and Avitabile et al [22] presented probability distribution functions skewed towards low biomass ranges, other studies [21,23,81] showed distributions tending towards much higher AGB levels, with averages two to three times larger than those found in this study and by Avitabile et al [22] (Figure 7). Figure 8 shows that the datasets from [21,23,81] did not adequately represent all the variations that exist in the area due to the lower spatial resolution and, also, generally showed a greater overestimation of the AGB. Although Santoro et al [81] provided more details in terms of the distribution of AGB in comparison with the other three maps, their map still overestimated the AGB compared to our results.…”
Section: Agb and Uncertainty Mapcontrasting
confidence: 78%
“…In the map developed in this study, one can observe the AGB variation in detail, which is corroborated by the observed high coefficient of determination (R 2 = 0.89) between the AGB reference datasets and the final AGB map. Figures 7 and 8 show the comparisons between the AGB estimates produced in our study and four other studies [21][22][23]81]. Although these maps were estimated using different methods and at different resolutions over the pantropical area, it is interesting to observe how the different data products compared to each other.…”
Section: Agb and Uncertainty Mapmentioning
confidence: 86%
See 3 more Smart Citations